2010
DOI: 10.1111/j.1939-1676.2010.0543.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Serum Ferritin as a Tumor Marker for Canine Histiocytic Sarcoma

Abstract: Background: Canine histiocytic sarcoma (HS) is an aggressive malignancy. Hyperferritinemia has been documented in dogs with HS and could serve as a tumor marker aiding in diagnosis and treatment. In people, hyperferritinemia is found in inflammatory diseases, liver disease, and hemolysis, and thus may occur in dogs with these conditions.Objective: To determine if serum ferritin concentration is a tumor marker for canine HS. Animals: Dogs with HS (18), inflammatory diseases (20), liver disease (24), immune-medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 22 publications
0
20
0
Order By: Relevance
“…Ferritin serves as both an iron storage protein and an acute phase reactant (Friedrichs et al, 2010). However, its significance in horses remains unclear (Smith et al, 1986;Hyyppä et al, 2002).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Ferritin serves as both an iron storage protein and an acute phase reactant (Friedrichs et al, 2010). However, its significance in horses remains unclear (Smith et al, 1986;Hyyppä et al, 2002).…”
Section: Discussionmentioning
confidence: 98%
“…Hyperferritinaemia occurs in people with haemolytic disorders and other diseases, such as malignancy and liver disease (Friedrichs et al, 2010). Ferritin content in animals is high in the spleen, liver, and bone marrow, but other tissue sources of ferritin, such as the heart and skeletal muscle have been less studied (Linder et al, 1981;Hyyppä et al, 2002).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In addition, the hyperferritinaemia found at J2 and J4 could be due to a stress response to exercise considering the well-known role of ferritin as an acute phase protein. The exercise-induced ferritin increase could be due to a tissue leakage of ferritin and in particular to splenic contraction but also to the increase of serum iron caused by intravascular haemolysis (Hyyppä et al 2002;Friedrichs et al 2010). The iron binding capacity of ferritin and its serum concentrations may be the first indicators of early iron deficiency (Ostojic and Ahmatovic 2008) which seems to be one of the most frequently encountered nutritional and/or exercise-related deficiencies in athletes.…”
Section: Discussionmentioning
confidence: 99%
“…Serum ferritin levels are altered in certain disease states, such as iron overload, inflammatory diseases, liver damage and malignancies [15]. In veterinary medicine, it has been reported that canine serum ferritin levels are increased in lymphoma, histiocytic sarcoma and immune mediate hemolytic anemia (IMHA) [3,7,10].…”
mentioning
confidence: 99%